Refleksi Nilai-Nilai Non Materi di Balik Penggunaan Pendapatan oleh Guru Honorer - Mohamad Anwar Thalib (Reviu Akuntansi, Manajemen, dan Bisnis, 2023)
Purpose: This study aims to reveal the non-material values behind the salary of honorary teachers. Methodology/approach: This research uses the Islamic paradigm. The approach used is Islamic ethnomethodology. There are five data analysis stages: charity, knowledge, faith, revelation information, and ihsan. The method used is qualitative, with data collection techniques in structured interviews and passive participatory observation. Results/findings: The results of the study show that there is a value of responsibility and worship behind the use of income by honorary teachers. This value of responsibility is reflected through the actions of honorary teachers in using their income to finance their personal and family needs. The value of worship is reflected in the decision of honorary teachers to use the income they earn for charity activities. Even if the income they earn is tiny, sufficient, or a lot, honorary teachers will continue to try to set aside the income they earn for charity. Limitations: This study was limited by the time available to collect data. The research was only carried out briefly; some important aspects may have yet to be revealed.. Contribution: The results of this research can be a basis for developing better education policies that consider non-material aspects of supporting honorary teachers and improving the quality of education.